2020
DOI: 10.1002/chem.202003782
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of Aromatic Nitrile Oxides and Nitrile Ylides: Potential Ring Expansion to Cycloheptatetraene Derivatives Mimicking Arylcarbenes

Abstract: Nitrile imines, nitrile oxides and nitrile ylides are widely used in 1,3‐dipolar cycloaddition reactions. They also undergo thermal and photochemical rearrangements to carbodiimides, isocyanates, and ketenimines, respectively. Calculations at DFT and CASPT2 levels of theory reveal novel, potential rearrangements, in which the aromatic 1,3‐dipoles mimic phenylcarbene and undergo ring expansion to cycloheptatetraene derivatives. These rearrangements can potentially take place in both the singlet ground states an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, it is more favorable still for the CSS nitrene to isomerize to HNCO via TS6 at 27.5 (33.3) kcal/mol. An analogous mechanism was determined for the rearrangement of benzonitrile oxide to phenyl isocyanate …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, it is more favorable still for the CSS nitrene to isomerize to HNCO via TS6 at 27.5 (33.3) kcal/mol. An analogous mechanism was determined for the rearrangement of benzonitrile oxide to phenyl isocyanate …”
Section: Resultsmentioning
confidence: 94%
“…An analogous mechanism was determined for the rearrangement of benzonitrile oxide to phenyl isocyanate. 49 Photolysis of matrix-isolated HCNO with a Xe arc lamp causes isomerization to HOCN (minor) and HNCO (major) on irradiation, whereby the reaction HCNO → HOCN was found to be faster that the reaction HNCO → HOCN. 20 It was therefore concluded that in the photolysis, HCNO isomerizes directly to HOCN, not via HNCO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrile imine 40 exists in the nonplanar, propargylic form 40a with a short (1.16 Å) CN bond and an N−N bond with a high degree of double-bond character (1.26 Å) in the singlet ground state (Figure 7B). The triplet states of nitrilium betaines are of much higher energies 21 and will not, therefore, be considered here. Due to the high degree of double-bond character, the cleavage of the N−N bond 22 does not occur under thermal conditions.…”
Section: Resultsmentioning
confidence: 99%